Pandemics, public policy, and Peltzman effects - Alexander Dietrich; Wilhelm Kohler; Gernot Müller (Economic Theory, 2024)
Against the backdrop of Covid-19, we study the effectiveness of public policies typically employed to fight an epidemic. We extend the compartmental SIR model to explore the trade-offs which govern individual behavior. Our stylized model allows for a closed form analysis of vaccination and lockdown policies. We establish Peltzman effects: as policies lower the risk of infections, people become more socially active, which—in turn—undermines their effectiveness. We detect patterns in data for both US states and countries in Western Europe that are consistent with the notion that such effects are shaping actual infection dynamics to a considerable extent.
Keywords: I12; I18; 330; Pandemic; Behavioral adjustment; SIR model; Risk compensation; Lockdowns; Vaccinations